CD Obesity‐Prone Rats, but not Obesity‐Resistant Rats, Robustly Ferment Resistant Starch Without Increased Weight or Fat Accretion. Issue 3 (21st February 2018) - Obanda, Diana; Page, Ryan; Guice, Justin; Raggio, Anne M.; Husseneder, Claudia; Marx, Brian; Stout, Rhett W.; Welsh, David A.; Taylor, Christopher M.; Luo, Meng; Blanchard, Eugene E.; Bendiks, Zach; et al.
Abstract : Objective: This study used CD obesity‐prone (OP) and obesity‐resistant (OR) rats to examine how weight gain and fat accretion relate to fermentation levels and microbiota composition after feeding resistant starch (RS). Methods: After feeding OP rats and OR rats a high‐fat (HF) diet for 4 weeks, rats were stratified into three groups: they were fed either an HF diet (group 1: HF‐HF) or were switched to a low‐fat (LF) diet (group 2: HF‐LF) or an LF diet supplemented with 20% RS by weight for 4 weeks (group 3: HF‐LFRS). Energy intake, body weight, fermentation variables, and microbiota composition were determined. Results: In OP rats, RS elicited robust fermentation (increased cecal contents, short‐chain fatty acids, and serum glucagon‐like peptide 1). Total bacteria, species of the Bacteroidales family S24‐7, and the archaean Methanobrevibacter smithii increased. The robust fermentation did not elicit higher weight or fat accretion when compared with that of control rats fed the same isocaloric diets (HF‐LF ± RS). In OR rats, body weight and fat accretion were also not different between HF‐LF ± RS diets, but RS elicited minimal changes in fermentation and microbiota composition. Conclusions: Robust fermentation did not contribute to greater weight. Fermentation levels and changes in microbiota composition in response to dietary RS differed by obesity phenotype.